2006
DOI: 10.1161/10.1161/01.hyp.0000209939.05482.61
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aging and Hypertension on the Microcirculation

Abstract: Abstract-Alterations of structure and function of the microcirculation in hypertension in the elderly and changes with normotensive aging have not been fully clarified. We studied capillary pressure, density, and skin microvascular function in 46 subjects in 3 groups: elderly subjects (aged Ͼ60 years) with untreated hypertension (nϭ16), elderly normotensive subjects (nϭ16), and young normotensive subjects (age Ͻ45 years, nϭ14). In a subgroup of 19 subjects, we also studied resistance artery function in the iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 26 publications
(35 reference statements)
4
49
0
Order By: Relevance
“…49 At variance with these reports, rarefaction was not found in dorsal finger skin of elderly subjects with mainly systolic hypertension. 11 There is some evidence that capillary rarefaction in the skin may antedate the clinical onset of essential hypertension. In 2 other studies by Antonios et al, 50 dorsal finger venous occlusion capillaroscopy revealed an abnormally low capillary density in borderline hypertensive subjects and even in normotensive subjects with a familial predisposition to the disease.…”
Section: Rarefaction In Clinical Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 At variance with these reports, rarefaction was not found in dorsal finger skin of elderly subjects with mainly systolic hypertension. 11 There is some evidence that capillary rarefaction in the skin may antedate the clinical onset of essential hypertension. In 2 other studies by Antonios et al, 50 dorsal finger venous occlusion capillaroscopy revealed an abnormally low capillary density in borderline hypertensive subjects and even in normotensive subjects with a familial predisposition to the disease.…”
Section: Rarefaction In Clinical Hypertensionmentioning
confidence: 99%
“…Except in specialized microvascular beds, such as the renal glomerulus, normal systemic capillary pressure (here, we disregard the pulmonary circulation, which is not relevant to the field of systemic hypertension) is relatively low (10 to 30 mm Hg). 11 Elevation of systemic capillary pressure above this range has several potentially deleterious effects, including the following: (1) interstial edema, which can have dramatic effects on the brain as exemplified in hypertensive encephalopathy 12 ; (2) disruption of capillary wall structure, with extravasation of plasma proteins and blood cells 13 ; and (3) activation of the microvascular endothelium, which may trigger or amplify an inflammatory cascade, 14 of importance, for example, in the pathogenesis of venous ulcers. 15 Pleiotropic changes in the functional behavior of arterioles have been noted in both clinical and experimental hypertension, including hyperresponsiveness to vasoconstrictor stimuli, 16,17 leading to their constriction or even complete closure, 16,18,19 endothelial dysfunction, 20,21 and reduced bioactivity of endothelium-derived NO.…”
mentioning
confidence: 99%
“…In hypertension elevated BP results in widespread 'remodelling' of small arteries and arterioles [6], a process that probably involves both functional and structural changes [7]. Remodelling contributes to the elevated peripheral vascular resistance that is a feature of established hypertension [8], but may also protect the microvasculature downstream from the elevated systemic blood pressure [9]. In the eye microvascular 'remodelling' is manifest as a narrowing of retinal arteriolar diameters [10][11][12] and reduced arteriolar density or number [11;13].…”
Section: Introductionmentioning
confidence: 99%
“…17 He et al 18 showed recently that modest salt reduction can restore capillary density in patients with mild hypertension. Shore and coworkers 19,20 have, in addition to capillary density, measured capillary pressures in the skin of hypertensive individuals. Capillary pressure was higher in both elderly normotensives and hypertensives than in young normotensives, suggesting a significant effect of aging rather than hypertension, per se, on capillary pressure.…”
Section: Capillaroscopymentioning
confidence: 99%